Aspek Hukum Pemberian HPL Atas Bidang Tanah Yang Telah Dikuasai, Diduduki Atau Digarap Oleh Warga - Felix Kurniawan (SAPIENTIA ET VIRTUS, 2019)
This article discusses the legal consequences of granting Management Rights (HPL) on land that has been controlled, occupied or cultivated by residents. The state as the highest holder of power over land, that power includes regulating and carrying out the designation, use, supply and maintenance of the earth, water and space; determine and regulate legal relations between people and earth, water and space; determine and regulate legal relations between people and legal actions concerning earth, water and space. On the basis of the state's right to control, there are various kinds of rights to the surface of the earth, called land, which can be given to and owned by people both alone and together with other people and legal entities. State power over land that is not owned by a person or other party's rights is wider and fuller. Decree of the State Minister for Agrarian Affairs / Head of the National Land Agency issues Decree No. 53 / HPL / BPN / 1997 concerning the Provision of HPL on behalf of the Surabaya Level II Municipal Government, even though the land has been controlled, occupied or cultivated by residents who have no legal basis.